Soluble oil adsorption onto modified chitosan beads - Jarupanavet Pornpimon; Piyamongkala Kowit (E3S Web of Conferences)
The adsorption soluble oil emulsion was studied in the laboratory scale. The effect of initial concentration of soluble oil to adsorb onto the surface of modified chitosan beads with 0.25 M hydrochloric acid solution was investigated. It was found that the maximum adsorption capacity soluble oil onto modified chitosan beads was 10,000 mg/g. The proton from hydrochloric acid which using as modified showed the role to destabilize soluble oil. The adsorption isotherm corresponded to the Langmuir equation.